Challenges for panel financial analysis - Cheng Hsiao (2018)
© Springer International Publishing Switzerland 2015. We consider panel financial analysis from a statistical perspective. We discuss some main findings and challenges in the area of (i) estimating standard errors; (ii) joint dependence; (iii) to pool or not to pool; (iv) aggregation and predictions; (v) modeling cross-sectional dependence; and (vi) multiple-dimensional statistics.